2019
DOI: 10.7554/elife.45183
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of randomized clinical trials in three medical journals reveals 396 medical reversals

Abstract: The ability to identify medical reversals and other low-value medical practices is an essential prerequisite for efforts to reduce spending on such practices. Through an analysis of more than 3000 randomized controlled trials (RCTs) published in three leading medical journals (the Journal of the American Medical Association, the Lancet, and the New England Journal of Medicine), we have identified 396 medical reversals. Most of the studies (92%) were conducted on populations in high-income counties, cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 84 publications
0
57
0
4
Order By: Relevance
“…Study reproducibility establishes confidence in the efficacy of therapies, while results that contradict original findings may lead to overturning previous standards. Herrera-Perez et al recently evaluated 396 medical reversals in which suboptimal clinical practices were overturned when randomized controlled trials yielded results contrary to current practices (2) . Given the evolving nature of evidence-based patient care, studies must be conducted in a way that fosters reproducibility and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Study reproducibility establishes confidence in the efficacy of therapies, while results that contradict original findings may lead to overturning previous standards. Herrera-Perez et al recently evaluated 396 medical reversals in which suboptimal clinical practices were overturned when randomized controlled trials yielded results contrary to current practices (2) . Given the evolving nature of evidence-based patient care, studies must be conducted in a way that fosters reproducibility and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…When faced with an unknown and frightening disease such as COVID-19, and given concerns over a potentially high case fatality rate, some clinicians and patients will feel strongly compelled to try unproven therapies based on theory, in vitro data, animal models, clinical anecdotes, observational studies confounded by severity, and uncontrolled or underpowered trials that may later be shown to be misleading. [1][2][3] For example, during the novel influenza A (H1N1) viral pandemic in 2009, countries stockpiled and used oseltamivir extensively, at great expense, based on data of suboptimal quality showing a potential benefit in patients admitted to hospital. 4 Even now, because there has been no RCT, it is not definitively known whether osel tamivir is efficacious for preventing or treating the complications of influenza in admitted patients.…”
mentioning
confidence: 99%
“…This occurs when we systematically devalue some types of knowledge over others, or give excessive/or too little credit to specific forms of testimony, or in her own words “[s]uch attributions are surely governed by no precise science, but clearly there can be error in the direction of excess or deficit.” For instance, EBM favours RCT, or other forms of “strong” evidence, over uncontrolled or less controlled studies, which constitute weaker forms of evidence. This is despite the fact that the results of strong evidence, such as RCTs, are often not replicable or are even contradicted by subsequent studies, and that drugs which initially appear beneficial subsequently are shown to provide little benefits or to be unsafe . In addition, such a naive favouring of “strong” evidence ignores the socio‐political realities and context of the research enterprise.…”
Section: Baseless Medicinementioning
confidence: 99%
“…This is despite the fact that the results of strong evidence, such as RCTs, are often not replicable or are even contradicted by subsequent studies, and that drugs which initially appear beneficial subsequently are shown to provide little benefits or to be unsafe. [17][18][19] In addition, such a naive favouring of "strong" evidence ignores the socio-political realities and context of the research enterprise. In this regard, it is noteworthy that John Ioannidis, a giant in the world of clinical epidemiology, felt it necessary to publish a thought piece on how EBM has been hijacked by vested interests.…”
Section: Introductionmentioning
confidence: 99%